(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Moreof the world’s income-poor live in India than any other country. Using aninternational poverty line of 1 per day (measured at a 1993 purchasing powerparity exchange rate), about one-third of the poor in the mid-1990s lived inIndia.1 What happens to poverty in India is quantitatively important to theworld’s overall progress in fightingabsolute poverty.